Konstruksi Toleransi pada Akun Media Sosial Jaringan Gusdurian - Danar Kristiana Dewi; Lulus Sugeng Triandika (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2020)
The role of tolerance is very important amid issues of division and radicalism. The spread of information on radicalism and extremism was met with resistance by many social organizations. They counter the issues of extremism and radicalism spread in society with issues of tolerance. This study aims to determine how tolerance messages are constructed on social media, especially on the Instagram account of Jaringan Gusdurian. This research employs qualitative approach with Entmant framing analysis techniques. Findings reveal that tolerance is constructed as a key to peace and unity in Indonesia. The problem of intolerance is caused by extremism. The moral values that legitimize tolerance are friendly religious Islam, solidarity transcendental insight of the Indonesian people. While the solutions offered to solve the problem of tolerance are caring for diversity and implementing the values of Pancasila in everyday life.Keywords: Framing analysis, Instagram, social media, and tolerance.